2005
DOI: 10.1159/000085044
|View full text |Cite
|
Sign up to set email alerts
|

Regional Specialization in Pyramidal Cell Structure in the Visual Cortex of the Galago: An Intracellular Injection Study of Striate and Extrastriate Areas with Comparative Notes on New World and Old World Monkeys

Abstract: Recent studies have revealed marked differences in the basal dendritic structure of layer III pyramidal cells in the cerebral cortex of adult simian primates. In particular, there is a consistent trend for pyramidal cells of increasing complexity with anterior progression through occipitotemporal cortical visual areas. These differences in pyramidal cell structure, and their systematic nature, are believed to be important for specialized aspects of visual processing within, and between, cortical areas. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…Cells become increasingly larger and more spinous with anterior progression through visual areas V1, V2, V4, TEO, and TE (Elston and Rosa, 1997, 1998; Elston et al, 1999b, 2005b,d,e; Elston, 2003b). Likewise, cells become increasingly larger and more spinous with progression through somatosensory areas 3b, 5, and 7 (Elston and Rockland, 2002; Elston et al, 2005h,i).…”
Section: Specialized Pyramidal Cell Growth Profiles Results In Specialmentioning
confidence: 99%
“…Cells become increasingly larger and more spinous with anterior progression through visual areas V1, V2, V4, TEO, and TE (Elston and Rosa, 1997, 1998; Elston et al, 1999b, 2005b,d,e; Elston, 2003b). Likewise, cells become increasingly larger and more spinous with progression through somatosensory areas 3b, 5, and 7 (Elston and Rockland, 2002; Elston et al, 2005h,i).…”
Section: Specialized Pyramidal Cell Growth Profiles Results In Specialmentioning
confidence: 99%
“…10F). Elston and collaborators (Elston et al, 1996(Elston et al, , 2005Elston, 2003), on the other hand, have compared the dendritic morphologies of layer 3 pyramidal neurons across several higher order visual areas in primates. Their detailed work showed that dendritic morphology of neurons becomes more complex as one proceeds along the hierarchy, but the neurons described were not retrogradely labeled through tracer injections to identify feedback neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In general, where neuron densities are highest (in V1 for example) the basilar dendritic spine densities are lowest, and where the neuron densities are lowest (in frontal and motor cortices) the spine densities tend to be the highest in all species of primates examined to date. Detailed examinations of pyramidal cell spine densities in visual cortical areas, including V1, V2, and more rostral extrastriate areas, show a predictable increase in spine densities in more rostral locations compared to V1 in prosimians [Elston et al, 2005] and New World [Elston et al, 1996] and Old World monkeys [Elston et al, 2006a]. In sensorimotor cortical areas in macaque monkeys there was a trend for increasing spine density and dendritic arbor complexity from S1 (3b), which has a relatively high neuron density and low spine densities, to nearby more caudally positioned areas such as somatosensory area 5 and parietal area 7b.…”
Section: Regional Variation In Cell Morphologymentioning
confidence: 94%